Quantifying atmospheric nitrogen deposition through a nationwide monitoring network across China - W. Xu; X. S. Luo; Y. P. Pan; L. Zhang; A. H. Tang; J. L. Shen; Y. Zhang; K. H. Li; Q. H. Wu; D. W. Yang; Y. Y. Zhang; J. Xue; et al. (Atmospheric Chemistry and Physics, 2015)
A Nationwide Nitrogen Deposition Monitoring Network (NNDMN) containing 43 monitoring sites was established in China to measure gaseous NH3, NO2, and HNO3 and particulate NH4+ and NO3− in air and/or precipitation from 2010 to 2014. Wet/bulk deposition fluxes of Nr species were collected by precipitation gauge method and measured by continuous-flow analyzer; dry deposition fluxes were estimated using airborne concentration measurements and inferential models. Our observations reveal large spatial variations of atmospheric Nr concentrations and dry and wet/bulk Nr deposition. On a national basis, the annual average concentrations (1.3–47.0 μg N m−3) and dry plus wet/bulk deposition fluxes (2.9–83.3 kg N ha−1 yr−1) of inorganic Nr species are ranked by land use as urban > rural > background sites and by regions as north China > southeast China > southwest China > northeast China > northwest China > Tibetan Plateau, reflecting the impact of anthropogenic Nr emission. Average dry and wet/bulk N deposition fluxes were 20.6 ± 11.2 (mean ± standard deviation) and 19.3 ± 9.2 kg N ha−1 yr−1 across China, with reduced N deposition dominating both dry and wet/bulk deposition. Our results suggest atmospheric dry N deposition is equally important to wet/bulk N deposition at the national scale. Therefore, both deposition forms should be included when considering the impacts of N deposition on environment and ecosystem health.